10 Autonomic Responses to Head Up Tilt in Patients with Syncope: The Influence of Ageing. (31st May 2014) - Patel, Hitesh; Middleton, Lee; Hayward, Carl; Sutton, Richard; Rosen, Stuart
Abstract : Introduction: Neurally mediated syncope is a common disorder but there remain large gaps in our understanding of its pathophysiology. Several groups have studied the role of the autonomic nervous system (ANS), baroreceptor sensitivity (BRS) and baroreceptor effectiveness (BEI) in syncope but have offered conflicting results. We hypothesised that patients who experience symptoms during head-up tilt testing (HUT) would have abnormal ANS and baroreceptor responses and that these changes may alter with advancing with age. Methods: We analysed HUT data from tests performed at Ealing Hospital between 2004–2012. These were clinically indicated HUT for individuals who experienced either syncope or pre-syncope. The Italian protocol was used during HUT. Beat-to-beat heart rate and non-invasive plethysmographic blood pressure monitoring was employed throughout, using the Task Force Monitor® (CN Systems, Graz, Austria). The device calculates short-term frequency domain heart rate variability (HRV) using an autoregressive algorithm, BRS using the sequence method and cardiac output using impedance cardiography. Results: HUT assessments in 298 patients were reviewed, there was no syncope in 187, 31 experienced syncope without GTN, 78 experienced syncope with GTN and 3 had carotid sinus syndrome (CSS). There was a bimodal age distribution for these HUT patients (Figure 1 ). CSS was found only in those > 60 years. There were differences across tertiles of age with respect to haemodynamics and ANS, BRS and BEI responses (Table 1 ). However, there were no differences, across tertiles of age, in the proportions of negative HUT, those positive without GTN and those positive with GTN (χ 2, p = 0.445). For the different stages of HUT, there were no significant differences in HRV and BRS between individuals who experienced syncope (with or without GTN) and those that did not. Conclusions: Autonomic nervous system variability and baroreceptor function at rest decline with age but this does not seem to influence the nature of syncope on HUT.